Agronomic biofortification - Cakmak, Ismail (International Food Policy Research Institute, 2014)
We assessed associations of maternal common mental disorders (CMD) with undernutrition and two common illnesses in children aged 0–5 years.Cross-sectional survey. Maternal CMD was measured using the WHO Self-Reporting Questionnaire-20. Child undernutrition was defined as stunting, underweight or wasting. Child illnesses included diarrhoea and acute respiratory infections (ARI). Multivariate logistic regression was used to test these associations adjusting for confounders at child, maternal and household levels.Bangladesh, Vietnam and Ethiopia.Mothers with children aged 0–5 years from 4400 households in Bangladesh, 4029 households in Vietnam and 3000 households in Ethiopia.The prevalence of maternal CMD was high, ranging from 31 % in Vietnam to 49 % in Bangladesh. Child undernutrition was more prevalent in Bangladesh and Ethiopia than in Vietnam. Symptoms of ARI and diarrhoea were also prevalent. In multivariate analysis, maternal CMD was associated with child stunting in Bangladesh (OR = 1·21; 95 % CI 1·03, 1·41) and with child underweight in Vietnam (OR = 1·27; 95 % CI 1·01, 1·61); no association was found with wasting. Maternal CMD was strongly associated with diarrhoea and ARI in all three countries.Maternal CMD, which affected nearly half of women in Bangladesh and one-third in Vietnam, was an important determinant of child stunting and underweight, respectively. No such association was found in Ethiopia, although CMD affected 39 % of women. Maternal CMD was strongly associated with childhood illnesses in all three countries. Interventions to support maternal mental health are important for women's own well-being and could make important contributions to improving child health and nutrition.